ELSA Speak Application as a Supporting Media in Enhancing Students’ Pronunciation Skill - Ita Sarmita Samad; Ismail Ismail (MAJESTY JOURNAL, 2020)
This research aimed at verifying the effectiveness of using ELSA Speak Application in enhancing students’ pronunciation skills. It applied a quantitative method. Specifically, it used a pre-experimental research design. The population was the English study program students of STKIP Muhammadiyah Enrekang. The sample was the first semester students in the academic year 2018/ 2019. It was chosen through purposive sampling technique by considering that the sample took the pronunciation course at that time. The data were collected through pre-test and post-test which was conducted using the recording. The data attained were analyzed statistically. The result shows that the pre-test means the score is 1.96 while the post-test mean score is 5.79 by applying 0.05 level of significance with 29 degrees of freedom (29), the t-test 6.28 was higher than the t-table 1.699. It indicated that the use of ELSA Speak application is effective in enhancing the pronunciation skill of the first semester students of STKIP Muhammadiyah Enrekang.